Assessment of Physico-Chemical Properties of Drinking Water in District Mardan, Khyber Pakhtunkhwa, Pakistan - Sayed Suliman Shah; Dawood Shah; Mujahid Islam; Wajahat Ali (Journal of Tropical Pharmacy and Chemistry, 2022)
The issue of water quality is becoming ever more serious as freshwater resources are severely degraded across the world. Water quality in rivers, streams, lakes, and subterranean aquifers is deteriorating, posing a threat to human life and ecological sustainability. A proper study of the physico-chemical properties of the water samples give us insight into the quality of life in a specific region, as poor water quality not only affects the aquatic life but the surrounding ecosystem as well. In the present study, 30 different water samples were collected from different regions of district Mardan and they were analyzed for their physico-chemical properties such as pH, total suspended solids, conductivity, total dissolved solids, nitrates concentration, sulphates concentration, chlorides concentration, dissolved oxygen, and biochemical oxygen demand. The results of the analysis show that most of the parameters have significantly higher values than the WHO permissible limits. From the analysis of water samples, the researchers have been able to designate the study area with poor water quality and to propose future advice for sustaining the water quality in the region.